Przezorność ubezpieczeniowa w zabezpieczeniu ryzyka starości - Worach-Kardas, Halina (The Old Age Risk and Insurance Cautiousness, 2008)
The purpose of this paper is to analyze the current state of insurance awareness and cautiousness in the light of old age risk. The article contains a general concept of life insurance functioning as one of the factors of financial security for the old age period in the new retirement system. The main factors and possibilities in developing the voluntary insurances by the Polish households are presented in the paper as well.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1197, s. 492-498